2005
DOI: 10.2320/matertrans.46.1278
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Quasicrystalline Particles in an Isothermally Aged Al–10Mg–0.5Ag (mass%) Alloy

Abstract: The quasicrystalline structure found in the isothermally aged microstructure in an Al-10Mg-0.5Ag (mass%) alloy after solution treated, water quenched and then aged during the time between 20 and 40 min at 240 C has been characterised using transmission electron microscopy, electron microdiffraction and energy dispersive x-ray spectroscopy. The morphology of the quasicrystalline precipitate particles is rhombohedral in shape and those precipitate particles are homogeneously nucleated, and finely and uniformly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…It thus remains that precipitate microstructures and precipitate phases in the ternary Al-Mg-Ag alloys during isothermal ageing are not thoroughly and convincingly understood. The purpose of this paper is to report results of a detailed microstructures examination of the metastable rod-like T precipitates phase transformed from the metastable quasicrystalline precipitate phase [13][14][15][16] during conventionally isothermal ageing process in an Al-10Mg-0.5Ag (mass%) alloy. Characterisation of structure and morphology of the metastable rod-like T precipitates phase was carried out using transmission electron microscopy with electron diffraction techniques.…”
Section: )mentioning
confidence: 99%
“…It thus remains that precipitate microstructures and precipitate phases in the ternary Al-Mg-Ag alloys during isothermal ageing are not thoroughly and convincingly understood. The purpose of this paper is to report results of a detailed microstructures examination of the metastable rod-like T precipitates phase transformed from the metastable quasicrystalline precipitate phase [13][14][15][16] during conventionally isothermal ageing process in an Al-10Mg-0.5Ag (mass%) alloy. Characterisation of structure and morphology of the metastable rod-like T precipitates phase was carried out using transmission electron microscopy with electron diffraction techniques.…”
Section: )mentioning
confidence: 99%
“…Early studies [8][9][10] suggested that the decomposition process might be summarised as follows: Supersaturated solid solution ( 12) as the equilibrium phase in the aged Al-Mg-Ag alloy. Recent studies of the microstructural observations by transmission electron microscopy (TEM), 13,14) however, revealed the formation of both the quasicrystalline phase rather than T 0 phase in the early stages and the equilibrium phase in over-aged conditions in Al-10Mg-0.5Ag (mass%) alloy.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen from these TEM micrographs, no fine-scale, uniformly distributed rod-like h110i particles, that were principally dispersed intermetallic compounds in the maximum hardness condition (i.e. 0.5 h at 240 C), [23][24][25][26] were observed, and they were replaced by coarse-scale precipitate particles, with two distinguishable morphologies. The dom- inant morphology was that of coarse-scale, irregularly globular particles, while there was a small volume fraction of finer-scale, spherical precipitates.…”
Section: Resultsmentioning
confidence: 99%
“…0.5 h at 240 C), [23][24][25][26] microstructures contained fine scale, uniformly distributed faceted particles. At the peak-aged stages of ageing (e.g.…”
Section: Resultsmentioning
confidence: 99%